2020
DOI: 10.1109/tcyb.2020.2990162
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 in China Using Hybrid AI Model

Abstract: The coronavirus disease 2019 (COVID-19) breaking out in late December 2019 is gradually being controlled in China, but it is still spreading rapidly in many other countries and regions worldwide. It is urgent to conduct prediction research on the development and spread of the epidemic. In this article, a hybrid artificial-intelligence (AI) model is proposed for COVID-19 prediction. First, as traditional epidemic models treat all individuals with coronavirus as having the same infection rate, an improved suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 31 publications
1
174
0
Order By: Relevance
“…Therefore, although medical imaging can make diagnoses faster, as stated above, it will be of limited use. Given this fact, new age techniques such as artificial intelligence (AI) [ [119] , [120] , [121] ] applications in medical imaging for tissue characterization can make computer-aided assessments and diagnoses faster. The main reason for this is that the AI can be scaled up to match the pandemic curve, thereby meeting the immediate demands of medical image diagnoses during the COVID-19 pandemic.…”
Section: The Role Of Imaging In Comorbid Patients With Covid-19mentioning
confidence: 99%
“…Therefore, although medical imaging can make diagnoses faster, as stated above, it will be of limited use. Given this fact, new age techniques such as artificial intelligence (AI) [ [119] , [120] , [121] ] applications in medical imaging for tissue characterization can make computer-aided assessments and diagnoses faster. The main reason for this is that the AI can be scaled up to match the pandemic curve, thereby meeting the immediate demands of medical image diagnoses during the COVID-19 pandemic.…”
Section: The Role Of Imaging In Comorbid Patients With Covid-19mentioning
confidence: 99%
“…Pinter et al [9] tried to predict the COVID-19 pandemic using ANFIS as well as MLP-imperialist competitive algorithm (MLP-ICA) models. Zheng et al [10] and Tomar and Gupta [11] used hybrid long short term memory (LSTM) models for COVID-19 prediction. Ribeiro et al [12] implemented several machine learning models for estimating COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… If the prevention regime changes, the MLP-ICA model will not maintain its accuracy 8. Zheng et al [10 ] China LSTM based hybrid model Significantly reduces the error of prediction. Long term prediction yet to be tested 9.…”
Section: Introductionmentioning
confidence: 99%
“…Procedures used in public transport could be extended to car sharing, due to the resembling nature of all these use cases, such as (a) periodic vehicle sanitation, (b) periods of time for ventilation every timeslot a car is used, or (c) regular precaution measures that have become widespread during the pandemic (usage of disposable or washable masks and gloves) are but a few of the actions that could take place. There are several research lines that can be suggested as future works in safe usage of shared private and public means of transport, like applying COVID−19 AI-based prediction models [78] for EVV2G sharing.…”
Section: Resultsmentioning
confidence: 99%